2005
DOI: 10.1515/jpem.2005.18.8.755
|View full text |Cite
|
Sign up to set email alerts
|

Beta-cell Autoantibodies and Diabetes Mellitus Family History in Cystic Fibrosis

Abstract: The investigated factors did not show correlation with the pathogenesis of CFRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…These results are in accordance with previous findings [24] and may reinforce the hypothesis that CF-related diabetes mellitus is not an autoimmune disease, but may be secondary to both insulin deficiency induced by pancreatic disease and insulin resistance induced by chronic infection [25]. Nevertheless, other studies have suggested that autoimmunity may play a role in the pathogenesis of CF diabetes, in the wake of bacterial hyperimmunisation [11].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with previous findings [24] and may reinforce the hypothesis that CF-related diabetes mellitus is not an autoimmune disease, but may be secondary to both insulin deficiency induced by pancreatic disease and insulin resistance induced by chronic infection [25]. Nevertheless, other studies have suggested that autoimmunity may play a role in the pathogenesis of CF diabetes, in the wake of bacterial hyperimmunisation [11].…”
Section: Discussionsupporting
confidence: 92%
“…Insulin resistance induced by chronic pulmonary infections has been proposed as a possible contributor to the development of CFRD [6] although this is also controversial [2]. Beta cell specific pancreatic autoantibodies are not more frequent in CFRD compared to the background population [7] and autoimmunity is not generally considered to be the mechanism as in type 1 diabetes (T1D). However, one study noticed the presence of islet cell antibodies in CF patients who were genetically predisposed with certain HLA-types with increased risk of developing autoimmune diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, there appears to be less similarity with type 1 diabetes, considering that diabetes incidence increases steadily with age rather than peaking in childhood, and that islet autoimmunity characteristic of type 1A diabetes plays little or no role in CF according to most (e.g. Minicucci et al [9], Lanng et al [10]) but not all (e.g. Nousia-Arvanitakis et al [11]) reports.…”
Section: Introductionmentioning
confidence: 99%